Adsorption of lead (II) from aqueous solution onto calcined volcanic ash - Siti Nor Atika Baharin, 1989-; Sugeng Triwahyono; Fakulti Sains (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012